Transferring knowledge into practice: a multi-modal, multi-centre intervention for enhancing nurses' infection control competency in Bangladesh. Issue 2 (June 2019) - Ara, L.; Bashar, F.; Tamal, M.E.H.; Siddiquee, N.K.A.; Mowla, S.M.N.; Sarker, S.A.
Summary: Background: Nurses are considered as the key to infection prevention as they play a major role in treatment as well as taking care of patients. Aim: To assess the role of a multi-modal intervention (MMI) in improving nurses' competency and adherence to standard infection control practices in Bangladesh. Methods: The study adopted a pretest–post-test intervention approach, in three different periods (from 2012 to 2017) in five hospitals (two public, two private, and one autonomous) in Bangladesh. Each study period was divided into three phases: pretest, MMI, and post-test. Data were collected on 642 nurses using direct observation method through a structured checklist. Findings: After implementing the MMI, overall hand hygiene compliance significantly increased before patient contact (from 1.3% to 50.2%; P < 0.000) and after patient contact (from 2.8% to 59.6%; P < 0.000). Remarkable improvements were also achieved in adherence to use of gloves (from 14.6% to 57.6%; P < 0.000), maintaining sterility of equipment during aseptic techniques (from 34.9% to 86%; P < 0.000), biomedical waste segregation (from 1.8% to 81.3%; P < 0.000) and labelling of procedural sites (from 0% to 85.7%; P < 0.000). Moreover, needlestick injury rate notably decreased (from 6.2% to 0.6%; P < 0.000). Conclusion: MMI can play a vital role in improving nurses' compliance with the standard infection control practices. Such context-specific interventions, which are crucial for preventing healthcare-associated infections and for decreasing occupational hazards, should be replicated in resource-poor countries for achieving universal health coverage by 2030.